Causal relationship between sea surface temperature and precipitation revealed by information flow - Ye, Ziyu; Tozuka, Tomoki (Frontiers in Climate, 2022)
The atmosphere and the ocean are coupled with each other through various processes. Therefore, it is of great importance to understand the causality relationship between the atmosphere and the ocean for predicting their states. Here we apply the Normalized Information Flow (NIF) to sea surface temperature (SST) and precipitation data to investigate the causality from the atmosphere to the ocean and from the ocean to the atmosphere. When the global spatial structure of the local NIFs is calculated for both directions, it is found that the ocean affects the atmosphere more in the tropics, while the atmosphere affects the ocean more in the extratropics. This causality relationship between the ocean and the atmosphere agrees with previous studies. To examine the teleconnections, the remote NIFs are then calculated and compared with the local NIFs. The local impact from SST to precipitation is dominant in almost all tropical regions, while the relative importance of remote impacts is higher for the precipitation-to-SST NIFs, except for a small area in the central-eastern equatorial Pacific and southeastern tropical Indian Ocean. Regional analyses for four selected areas within the Indian and Pacific Oceans are also presented. This study suggests that NIFs may be a powerful tool to study ocean-atmosphere interactions.